Systematic Review and Dosage Analysis: Hyperbaric Oxygen Therapy Efficacy in Mild Traumatic Brain Injury Persistent Postconcussion Syndrome - Harch, Paul G. (Frontiers in Neurology, 2022)
Background Mild traumatic brain injury results in over 15% of patients progressing to Persistent Postconcussion Syndrome, a condition with significant consequences and limited treatment options. Hyperbaric oxygen therapy has been applied to Persistent Postconcussion Syndrome with conflicting results based on its historical understanding/definition as a disease-specific therapy. This is a systematic review of the evidence for hyperbaric oxygen therapy (HBOT) in Persistent Postconcussion Syndrome using a dose-analysis that is based on the scientific definition of hyperbaric oxygen therapy as a dual-component drug composed of increased barometric pressure and hyperoxia. Methods In this review, PubMed, CINAHL, and the Cochrane Systematic Review Database were searched from August 8–22, 2021 for all adult clinical studies published in English on hyperbaric oxygen therapy in mild traumatic brain injury Persistent Postconcussion Syndrome (symptoms present at least 3 months). Randomized trials and studies with symptomatic and/or cognitive outcomes were selected for final analysis. Randomized trials included those with no-treatment control groups or control groups defined by either the historical or scientific definition. Studies were analyzed according to the dose of oxygen and barometric pressure and classified as Levels 1–5 based on significant immediate post-treatment symptoms or cognitive outcomes compared to control groups. Levels of evidence classifications were made according to the Centre for Evidence-Based Medicine and a practice recommendation according to the American Society of Plastic Surgeons. Methodologic quality and bias were assessed according to the PEDro Scale. Results Eleven studies were included: six randomized trials, one case-controlled study, one case series, and three case reports. Whether analyzed by oxygen, pressure, or composite oxygen and pressure dose of hyperbaric therapy statistically significant symptomatic and cognitive improvements or cognitive improvements alone were achieved for patients treated with 40 HBOTS at 1.5 atmospheres absolute (ATA) (four randomized trials). Symptoms were also improved with 30 treatments at 1.3 ATA air (one study), positive and negative results were obtained at 1.2 ATA air (one positive and one negative study), and negative results in one study at 2.4 ATA oxygen. All studies involved <75 subjects/study. Minimal bias was present in four randomized trials and greater bias in 2. Conclusion In multiple randomized and randomized controlled studies HBOT at 1.5 ATA oxygen demonstrated statistically significant symptomatic and cognitive or cognitive improvements alone in patients with mild traumatic brain injury Persistent Postconcussion Syndrome. Positive and negative results occurred at lower and higher doses of oxygen and pressure. Increased pressure within a narrow range appears to be the more important effect than increased oxygen which is effective over a broad range. Improvements were greater when patients had comorbid Post Traumatic Stress Disorder. Despite small sample sizes, the 1.5 ATA HBOT studies meet the Centre for Evidence-Based Medicine Level 1 criteria and an American Society of Plastic Surgeons Class A Recommendation for HBOT treatment of mild traumatic brain injury persistent postconcussion syndrome.